Adaptation and Evaluation of the Nutrition Environment Measures Survey in Stores to Assess Mediterranean Food Environments (NEMS-S-MED) - Martínez-García, Alba (Int J Environ Res Public Health, 2020)
The Nutrition Environment Measures Surveys are valid and reliable measures of community and consumer food environments. This article describes the adaptation and evaluation of the Nutrition Environment Measures Survey in Stores (NEMS-S) for Mediterranean urban contexts (NEMS-S-MED). Trained raters used the adapted NEMS-S-MED tool to observe and rate food outlets in 21 census tracts and 43 food stores across the city of Madrid, Spain. We evaluated inter-rater and intra-rater reliabilities, construct validity, and the tool’s ability to discriminate between store types and between stores by area-level Socio-Economic Status (SES). Overall, the mean NEMS-S-MED score was 20.7 (SD = 9.8), which ranged from 7 to 43. Most food items displayed substantial or almost perfect inter-rater and intra-rater agreements; the percentage agreement across availability items was almost perfect and kappa statistics were also very high (median κ = 1.00 for inter-rater; κ = 0.92 for intra-rater). Furthermore, the NEMS-S-MED tool was able to discriminate between store types and census tracts of different SES. The adapted NEMS-S-MED instrument is a reliable and valid audit tool to assess the consumer food environment in Mediterranean urban contexts. Well-constructed measurement tools, such as the NEMS-S-MED, may facilitate the development of effective policy interventions to increase healthy food access and affordability.